PERBANDINGAN EFEKTIVITAS MADU DAN EKSTRAK ETANOL DAUN KELOR (MORINGA OLEIFERA LAMK) TERHADAP PERCEPATAN PENYEMBUHAN LUKA BAKAR DERAJAT II PADA TIKUS PUTIH JANTAN (RATTUS NORVEGICUS STRAIN WISTAR) SECARA MAKROSKOPIS - Muhammad Azmi Fanany; Andi Ipaljri Saputra; Wifa Nur Yasmin (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: Burns are damage to the skin or other tissues caused by high temperatures, radiation,electricity, or contact with chemicals. Healing by maintaining resistance that has potential to killbacteria at affordable prices is to use the active substances contained in honey and Moringa leaf.Methods: Research with True Experimental design by giving honey and ethanol extract of moringaleaves in gel preparation to affect the acceleration of second degree burn wound healing in ratsmacroscopically. With the design of "Post Test Only Control Group Design". The data were analyzedusing the Mann Whitney nonparametric test.Result: Analysis of data on the average diameter of wound healing and percentage of wound reductionon day 7 between honey and ethanol extract of moringa leaves with a significance value of 0.000, onday 14 a significance value of 0.000 was obtained which means sig.<0.005 It can be concluded thereis a significant difference between the treatment groups.Conclusion: Ethanol extract of moringa leaves has a smaller wound diameter value, which is anaverage of 12.09 mm compared to honey which has a wound diameter of 14.54 mm. Based on thepercent reduction value, moringa leaf ethanol extract has a percent wound reduction of 39.90%compared to honey which has a percent wound reduction value of 27.26%.